Atomic-scale engineering of MOF array confined Au nanoclusters for enhanced heterogeneous catalysis. Issue 3 (2nd January 2019) - Gao, Ge; Xi, Qiaoyue; Zhang, Yanqun; Jin, Manyu; Zhao, Yongxia; Wu, Cunqi; Zhou, Hua; Guo, Pengran; Xu, Jingwei
Abstract : A surface-engineered heterogeneous catalyst with a controllable catalytic interface is the most straightforward approach for boosting catalytic activity. Abstract : A surface-engineered heterogeneous catalyst with a controllable catalytic interface is the most straightforward approach for boosting catalytic activity. However, changing the surface structure of nanocrystals and ensuring the exposure of active sites still face challenges. In this work, a three-dimensional self-supported catalyst with ultrathin Au nanoclusters encapsulated in Cu-doped ZIF-8 nanorod arrays on Ni foam (AuNC @ZIF-8(Cu) NRAs) is synthesized by a bottom-up strategy. This catalyst exhibits high catalytic activity with a 98% conversion of 4-nitrophenol to 4-aminophenol within 6 min. Meanwhile, it also has superior catalytic activity for other nitrobenzene compounds, such as 3-nitrophenol, 2-nitrophenol and p -nitroaniline. Furthermore, after 10 cycles, the catalytic performance and morphology of the catalyst have no obvious change. The excellent catalytic performance and stability of AuNC @ZIF-8(Cu) NRAs are attributed to the synergistic effect of ZIF-8(Cu) and AuNC . The doping of Cu in the ZIF-8 framework effectively alters the superficial electronic structure of encapsulated Au nanoclusters, which can dramatically promote the formation of gold hydride intermediates. The confinement effect of the porous ZIF-8 framework makes the AuNC active sites more stable and accessible to substrates. This method can be used to alter the activity of the catalyst by regulating the metal ion coordination of MOFs to influence the surface properties of encapsulated AuNC and opens the door to the rational design of new catalysts.